FRI0565 Eramrs: a new mr scoring system for early rheumatoid arthritis. (12th June 2018) - Xiao, F.; Yue, J.; Tam, L.-S.; Griffith, J.
Abstract : Background: Early rheumatoid arthritis (ERA) is defined as having symptoms for less than 24 months and MRI allows quantification of several inflammatory features of ERA. Due to inclusion of some less relevant MR features and non-inclusion of other more relevant features, three MRI scoring systems currently employed are not ideally suited for use in ERA. We therefore devised a new more inclusive system suited for ERA, known as the ERA MR score ('ERAMRS'). The clinical relevance of this new ERAMRS system over the other MR scoring systems can be gauged by seeing how well these MR scoring systems correlate with clinical scoring systems. Objectives: To (a) introduce a new scoring system (ERAMRS) for measuring the degree of inflammation on MR in early rheumatoid arthritis (RA) and (b) to see how well this ERAMRS system correlates with clinical scoring systems and serological parameters compared to currently used MR scoring systems. Methods: 106 patients (81 females, 25 males, age, 53±12 years) with early (i.e. symptoms<24 months) untreated RA underwent clinical/serological testing as well as 3T MRI of the most symptomatic wrist. Clinical assessment included Patient Global Assessment (PtGA), Physician Global Assessment (PGA) and Simple Disease Activity Index (SDAI). Erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) were also measured. ERAMRS (Early Rheumatoid Arthritis Magnetic Resonance Score) was semi-quantitatively assesses wrist joints synovitis (no=0, mild=1, moderate=2, severe=3) and enhancement (no=0, mild=1, moderate=2, severe=3), tenosynovitis (no=0, mild=1, moderate=2, severe=3) and enhancement (no=0, mild=1, moderate=2, severe=3) as well as bone marrow oedema (no=0, <50% of the whole bone=1, >50% of the whole bone=2). Seven wrist joints, nine wrist tendons as well as 15 wrist bones were assessed. This ERAMRS method was compared to currently used methods of scoring inflammation on wrist MRI ('RAMRIS'[, 1 'McQueen'[, 2 and 'MRI detected inflammation score'[ 3 ). Results: Synovitis was present in 104 (98%), bone marrow oedema in 77 (73%), and tenosynovitis in 82 (77%) of the 106 wrists at presentation. RAMRIS system had the lowest correlation (PtGA, PGA, SDAI, CRP) or no correlation (ESR) while the ERAMRS system had the highest correlation with clinical disease activity level scoring systems (r=0.44, p<0.001) and serological parameters (r=0.41, p<0.001) among these four scoring systems. Conclusions: The ERAMRS system, designed to grade inflammation on wrist MRI in early RA, provided the best correlation with clinical scoring systems and serological parameters indicating its improved clinical relevance over other MR scoring systems. References: [1] Østergaard M, et al. An introduction to the EULAR–OMERACT rheumatoid arthritis MRI reference image atlas. Ann. Rheum. Dis. 2005Feb;64(suppl 1):i3–i7. [2] Burgers LE, et al. Magnetic resonance imaging-detected inflammation is associated with functional disability in early arthritis—results of a cross-sectional study. Rheumatology2016Dec;55(12):2167–2175. [3] McQueen FM, et al. Magnetic resonance imaging of the wrist in early rheumatoid arthritis reveals a high prevalence of erosions at four months after symptom onset. Ann. Rheum. Dis. 1998Jun;57(6):350–356. Acknowledgements: NA Disclosure of Interest: None declared